Cost Effectiveness of Voretigene Neparvovec for RPE65-Mediated Inherited Retinal Degeneration in Germany - Uhrmann, Matthias Fritz (Transl Vis Sci Technol, 2020)
PURPOSE: Voretigene Neparvovec-rzyl (VN) is the first available treatment for biallelic RPE65 mutation-associated inherited retinal degeneration, which is usually associated with infancy-onset severe visual impairment and complete blindness during the third life decade. We aim to estimate the cost effectiveness of VN in Germany considering medication costs of €410,550 per eye and potential indirect cost offsets by higher labor force participation. METHODS: We developed an individual patient sampling model to simulate patients over their lifetime. In a Monte Carlo analysis, 1000 simulations are performed. Cycle length of the two-state Markov model is 1 year. For each cycle, visual field and best-corrected visual acuity are tracked, compared with natural progression and converted to quality of life. Direct and indirect costs are recorded and the incremental cost-utility ratio is calculated. RESULTS: In the base case scenario, VN provides 4.82 additional quality-adjusted life-years over a patient's lifetime at an incremental cost-utility ratio of €156,853 per additional quality-adjusted life-year gained. Sensitivity analyses show the robustness of the results when altering treatment effect duration, discounting of quality-adjusted life-years and costs, direct costs, and natural progression. CONCLUSIONS: Under a lifetime perspective, VN proves to be cost effective for the German statutory health insurance system despite high initial treatment costs. Because VN has important implications for future gene therapies, cost-utility analyses have high economic relevance from a societal perspective. TRANSLATIONAL RELEVANCE: Our research analyzes the value of a gene augmentation therapy in clinical care in terms of quality of life gains for patients with blindness from retinal degeneration.